Serpenteando por narrativas ancestrais: análise semiótico-discursiva do jogo Huni Kuin: Yube Baitana - Duarte, Mayara Benevenuto (2024)
This research focuses on the semiotic analysis of a videogame called Huni Kuin: Yube Baitana (the ways of the boa-constrictor), a collective creation by a team of (non-indigenous) researchers and technicians and the Huni Kuin people involved in the project. To carry out this research, we started with the following question: What identity and cultural values of the Huni Kuĩ people are present in the game Huni Kuin: Yube Baitana? In conjunction with this question, we aimed to study the structure and discursive functioning of the game. The general objective was to investigate, based on Greimas (1966, 2018) analysis of semiotic discourse, how the ancestral narratives of the Huni Kuĩ people are represented in the game Yube Baitana. The specific objectives are: (1) to articulate the theoretical and methodological conceptions of discursive semiotics, especially with regard to the generative path of signification and visual semiotics, focusing on the enunciative and figurative elements that are constructed in the game; (2) to investigate the values and worldviews of the Huni Kuĩ people implicated in the game with an emphasis on identity and cultural aspects; (3) to deduce the meanings of the values and worldviews of the Huni Kuin peoples imbricated in the game through the generative path of signification and visual semiotics. The universe of this work is the Huni Kuin game Yube Baitana, made up of five stories told by older Huni Kuĩ people. Of the five, we selected the first story entitled Huã Karu Yuxibu. In terms of procedures, this research proposal is bibliographical (Prodanov; Freitas, 2013), and the approach is qualitative. In addition, it followed the methodology of French semiotics; added to the decolonial theoretical discussions of Bispo dos Santos (2006) and Krenak (2012), Maldonado-Torres (2007), Mignolo (2000, 2017), Lélia Gonzalez (1988) and the discussions on games by Caillois (1990) and Huizinga (1999). The data analysis reveals a wealth of cultural and identity elements of the Huni Kuĩ people, highlighting the importance of ancestry, the preservation of traditions and the transmission of knowledge. The syncretic analysis reinforces these findings through the symbolic use of colors and cultural icons, underlining the community's strong connection with its natural environment and ritual practices. These elements contribute to a dense and rich narrative, revealing the depth of the Huni Kuĩ's cosmology and worldview.